2019
DOI: 10.1080/02713683.2019.1669664
|View full text |Cite
|
Sign up to set email alerts
|

Neuroinflammation and Optic Nerve Regeneration: Where Do We Stand in Elucidating Underlying Cellular and Molecular Players?

Abstract: Neurodegenerative diseases and central nervous system (CNS) trauma are highly irreversible, in part because adult mammals lack a robust regenerative capacity. A multifactorial problem underlies the limited axonal regeneration potential. Strikingly, neuroinflammation seems able to induce axonal regrowth in the adult mammalian CNS. It is increasingly clear that both blood-borne and resident inflammatory cells as well as reactivated glial cells affect axonal regeneration. The scope of this review is to give a com… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
15
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(15 citation statements)
references
References 164 publications
0
15
0
Order By: Relevance
“…As such, the spontaneously regenerating adult zebrafish provides the ideal model organism to further disentangle which different cells and molecules contribute to the proregenerative outcome of inflammatory stimulation. A first query to be tackled is the identification and role of the different immune cell types at play during the regenerative process, which still remains a matter of debate (Andries et al, 2020). In this view, Tsarouchas et al (2018), who used different transgenic and mutant zebrafish lines, reported that neutrophil‐derived il‐1β first promotes but thereafter counteracts axonal regrowth after spinal cord injury.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…As such, the spontaneously regenerating adult zebrafish provides the ideal model organism to further disentangle which different cells and molecules contribute to the proregenerative outcome of inflammatory stimulation. A first query to be tackled is the identification and role of the different immune cell types at play during the regenerative process, which still remains a matter of debate (Andries et al, 2020). In this view, Tsarouchas et al (2018), who used different transgenic and mutant zebrafish lines, reported that neutrophil‐derived il‐1β first promotes but thereafter counteracts axonal regrowth after spinal cord injury.…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, Irf8 mutant zebrafish larvae, with strongly reduced numbers of microglia/macrophages, were found to display a defective functional recovery, while axonal regeneration remained unaffected in microglia‐deficient csf1ra/b larvae (Tsarouchas et al, 2018). These results suggest that a biphasic inflammatory response, with an early proinflammatory phase (dominated by neutrophils) followed by a late anti‐inflammatory phase (with macrophages as the primary actors), might be necessary at the site of injury for successful regeneration (Andries et al, 2020; Tsarouchas et al, 2018). Also in our study, neutrophils were the first cells to be detected in the inflamed retina and were present throughout the early inflammatory response.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the first week following ONC the inflammatory response reaches its peak. Infiltrating monocyte-derived macrophages arrive at the optic nerve after the first day (5,48). Of note, immunohistochemical classification of microglia vs. macrophages (and thus, their relative contributions) remains difficult, as macrophages take on a microglia-like molecular profile upon infiltration and activation in the CNS (49,50); however, recent retinal single-cell profiling experiments have made huge strides in determining the full complement of different myeloid cells involved in injury responses (51).…”
Section: The Critical First Weekmentioning
confidence: 99%
“…However, knowledge about axonal destruction and regeneration is fast accumulating, bringing us closer to developing regenerative therapies for CNS tissues. Many other excellent reviews have covered the topic of RGC regeneration (1)(2)(3)(4)(5), each from its own perspective. Some discuss the generation and transplantation of new RGCs; others investigate potential pro-regenerative paracrine effects of mesenchymal stem cell replacement therapies (6,7).…”
Section: Introductionmentioning
confidence: 99%